Performance measurement system, organisational learning and business unit performance in Islamic Banks - Ataina Hudayati; Sofiah Md Auzair (FEP, 2011)
This study examines the relationship between performance measurement systems (PMS), business unit, and profit and loss sharing (PLS) financing performance in Islamic Banks. Two elements of PMS were studied –strategic PMS and interactive use of PMS. Utilising the survey method, questionnaires were mailed to 256 business units of Islamic Banks in Indonesia, of which 99 were returned. Employing the resourced-based view, it is expected that the effect of PMS on both performances is indirect through organisational learning. Nevertheless, strategic PMS is also expected to have a direct relationship with business unit performance. Tested using Partial Least Squares regression, the results indicate that the interactive use of PMS is indirectly related to performances through organisational learning. Strategic PMS was found to be directly related to business unit performance. The findings highlight the role of PMS in enhancing organisational learning in Islamic Banks, which translates into high performance.